A new method to protect the cementing sealing integrity of carbon dioxide geological storage well: An experiment and mechanism study. (September 2020) - Li, Cheng; Guan, Zhichuan; Zhao, Xiaofeng; Yan, Yan; Zhang, Bo; Wang, Qing; Sheng, Yanan
Highlights: A new measure for protecting cementing sealing integrity is developed. The new experimental device has a full-scale simulative wellbore unit. The failure modes of cement sheath are only the radial fractures under the influence of protective layer. The protective layer can help the cement sheath bear extra 19.4 MPa of casing pressure. The protective layer can reduce the expansion extent of plastic zone of the cement sheath. Abstract: It is one of the important technical difficulties to improve the cementing sealing capacity of the carbon dioxide (CO2 ) injection well for ensuring the long-term effective of the CO2 geological storage. The two experiments with and without protective layer were conducted under the conditions of 10 MPa confining pressure and 70 °C environmental temperature. The casing pressure gradually increased from 10 MPa, and the channeling detection pressure was 10 MPa. According to the physical properties of the materials and the environment conditions applied in the experiments, two 2D finite element models of casing-cement-formation system for these two experiments were built respectively, and the failure modes of the cement sheaths in the experiments were analyzed. As shown in the experiments, the maximum casing pressure that the cement sheath in the experiment with protective layer can bear is 19.4 MPa higher than that of another experiment. According to the finite element analysis, the maximum Von-Mises stress of the cement sheaths had all not reached the yield strength of 15.2 MPa before failed, thus no plastic deformation or micro-annulus had occurred. During the casing pressure in these two experiments increasing from 40 MPa to 50 MPa and from 20 MPa to 30 MPa respectively, the cement sheaths begin to produce tensile failure. If ignoring the actual failures of the cement sheaths and continuously increasing the casing pressure in the finite element analysis, the cement sheathes in the two models will produce plastic deformation when the casing pressure reaching 93 MPa and 57 MPa respectively. Therefore, this preventive measure is effective to protect the cementing sealing integrity of CO2 injection well.